STUDI PEMETAAN POLITIK DAN PERILAKU PEMILIH PADA PEMILIHAN UMUM KEPALA DAERAH DI KOTA PALEMBANG - Markoni Markoni (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2014)
The research is aimed to explore political Map and voter behaviour. This research is to identify  factors that influence voters in determining their choice to candidates.   It is merely case study whereas the research are mainly focus  on Major District General election in Palembang. The main research problems to be explored are concerning with  the important factors  that influence voters in determining their choice to candidates. The research mainly used primary data by delivering questionaires to selected respondents. The questionaire was delivered to 1070 selected respondents. It is also used secondary data to enrich the research analysis. Research finding shows  that popularity and electability Romi Herton  are higher among other candidats. It is also found that most voters are remain floating. In line with survey, newspaper is one of media used by voters as information sources that influence voters in determining their choice.  the main  factors  effected  voters in choosing Major candidates